Public Policy and the Politics of Open Access - Prosser, David C. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
In the five years since the launch of the Budapest Open Access Initiative in February 2002, one of the most striking developments in the scholarly communications landscape has been the increasing interest taken in open access at a policy level. Today, open access (in the form of both self-archiving and open access journals) is routinely discussed and debated at an institutional-level, within research-funding bodies, nationally, and internationally. The debate has moved out of the library and publisher communities to take a more central place in discussions on the ‘knowledge economy’, return on investment in research, and the nature of e-science. This paper looks at some of the public policy drivers that are impacting on scholarly communications and describes the major policy initiatives that are supporting a move to open access.